Penggunaan Inhibitor Dari Ekstrak Daun Ketapang (Terminalia Catappa L) Dengan Metode Sokletasi Untuk Mengendalikan Laju Korosi Pada Baja Karbon ASTM A36 - Mastiar Krisdayanti Sinaga; Komalasari Komalasari; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Corrosion has been identified as one of the major problems in the chemical industry, especially in the pipeline’s system. The inhibitor is the most effective way to protect the metal against corrosion. The natural corrosion inhibitor is chosen as an alternative because it’s safe, widely available, low cost, biodegradable and environmentally friendly. This study aims to know the corrosion rate and the inhibition efficiency of Terminalia Catappa L leaf extract for low carbon steel. Terminalia Catappa L leaf extract was obtained by soxhlet extraction using ethanol-water as the solvent. Corrosion rate were determined by using the weight loss method. Low carbon steel was immersed in HCl 0.1 0.5 m and 1 M with and without Terminalia Catappa L leaf extract 0 g/L and 1.5 g/L by immersion time 24, 48,72,96 h. The result showed that corrosion rate decreases on increasing of concentration of the extract and increases the inhibition efficiency. The maximum efficiency was obtaining at 1.5 g/L of corrosion inhibitor of 96 hours contact time in HCl 0.1 M with inhibition efficiency 89,77%. Keywords: corrosion, HCl, inhibitor, low carbon steel, Terminalia Catappa L leaf